A study on knowledge, attitude and practice of hand hygiene among medical students at a tertiary care center in Indore - Singh, Bharat; Kumar, Amit; Bajpai, Trupti; Pargi, Pankti; Kishori, Rekha; Patanvadia, Dipak (International Journal Of Community Medicine And Public Health, 2025)
Background: Hand hygiene is a critical global healthcare issue and a proven cost-effective measure to reduce healthcare-associated infections. Assessing awareness and compliance among healthcare workers is therefore essential. Aim was to evaluate the knowledge, attitude, and practice (KAP) of hand hygiene among final-year medical students and its association with selected variables. Methods: A cross-sectional study was conducted among 270 final-year medical students at a tertiary care teaching hospital in Indore, central India. Knowledge, attitude, and practices related to hand hygiene among previously trained and untrained participants were assessed using a self-administered questionnaire, including the WHO hand hygiene knowledge assessment tool. Data were entered into Microsoft Excel and analyzed using the Chi-square test. A p value <0.05 was considered statistically significant. Results: Overall, participants demonstrated moderate knowledge, attitude, and practice of hand hygiene. Among trained students, 55.7% had adequate knowledge compared to 49.6% of untrained students. Similarly, a positive attitude was observed in 61% of trained versus 51.7% of untrained students. Practice compliance was also higher among trained participants (59.5%) than untrained ones (56.8%). Although both groups showed moderate responses, trained students consistently outperformed untrained peers. Conclusions: The study highlighted the need for rigorous and comprehensive training programs on hand hygiene. Regular reinforcement of hand hygiene techniques can motivate medical students and ensure they remain updated on current best practices. Effective training during medical education may significantly improve compliance and reduce healthcare-associated infections.